US3/Rps3 controls fidelity of translation termination and programmed stop codon readthrough in co-operation with eIF3. Issue 21 (23rd October 2019) - Poncová, Kristýna; Wagner, Susan; Jansen, Myrte Esmeralda; Beznosková, Petra; Gunišová, Stanislava; Herrmannová, Anna; Zeman, Jakub; Dong, Jinsheng; Valášek, Leoš Shivaya
Abstract: Ribosome was long considered as a critical yet passive player in protein synthesis. Only recently the role of its basic components, ribosomal RNAs and proteins, in translational control has begun to emerge. Here we examined function of the small ribosomal protein uS3/Rps3, earlier shown to interact with eukaryotic translation initiation factor eIF3, in termination. We identified two residues in consecutive helices occurring in the mRNA entry pore, whose mutations to the opposite charge either reduced (K108E) or increased (R116D) stop codon readthrough. Whereas the latter increased overall levels of eIF3-containing terminating ribosomes in heavy polysomes in vivo indicating slower termination rates, the former specifically reduced eIF3 amounts in termination complexes. Combining these two mutations with the readthrough-reducing mutations at the extreme C-terminus of the a/Tif32 subunit of eIF3 either suppressed (R116D) or exacerbated (K108E) the readthrough phenotypes, and partially corrected or exacerbated the defects in the composition of termination complexes. In addition, we found that K108 affects efficiency of termination in the termination context-specific manner by promoting incorporation of readthrough-inducing tRNAs. Together with the multiple binding sites that we identified between these two proteins, we suggest that Rps3 and eIF3 closely co-operate to control translation termination and stop codon readthrough.